Wzory działalności zawodowej pracowników socjalnych ośrodków pomocy społecznej = Models of the professional activity of social aid centres workers - Lipowicz, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author discusses the result of research on social workers` activity. She describes in detail the range of their tasks, attitudes towards innovations, rationality and professional ethics. The conclusion presents a description of typical social workers` activity models.
Keywords: województwo lubuskie; pomoc społeczna; ośrodki pomocy społecznej; pracownicy